KONSTRUKSI, IMPLEMENTASI, DAN MODEL PENEGAKAN HUKUM TERHADAP ANAK RESIDIVIS TINDAK PIDANA PENCURIAN DALAM SISTEM PERADILAN PIDANA ANAK - Udjari, Hendrianto; Waskito, Sarwo; Wijaya, Kurnia; Mujito, Mujito; Suwito, Suwito (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study discusses the construction of formal law, the implementation of law enforcement, and the ideal law enforcement model for recidivist children of theft based on Law Number 11 of 2012 concerning the Child Criminal Justice System. The formal legal construction affirms child protection through diversion, restorative justice, and coaching mechanisms in Special Children's Development Institutions. Implementation in court shows a balance between repressive and rehabilitative aspects, with judges considering community research and children's right to legal assistance. The ideal law enforcement model emphasizes the integration of child protection, educational penal goals, and the involvement of families and communities in the coaching process. The overall analysis confirms that the child recidivist of theft should be treated as an individual who still has a chance to be corrected, not simply as a perpetrator to be punished.